La Bibbia in aramaico. Verso una mutua definizione di Giudaismo e Cristianesimo - Bissoli, G. (Liber Annuus, 2000)
Abstract Apart from the fact that the Palestinian Targum presents the Scripture as actually read in the Synagogue, can we find in them traces of the early Christian community! Since they took written form in the second century AD onwards, especially addressing problems of the Synagogue, one may not expect much to respond to this curiosity. There are polemic aspects, directed rather against particular points in the Scripture from which the “nosrim” - and above all the gnostics - draw hints for their own doctrine than against the Christian community in itself. The polemic is so hidden that only by knowing heterodoxical interpretations of a text is it possible to understand how the Targum means to defend its community. Nevertheless it is during the time of Origen’s residence at Caesarea that we have the greatest number of witnesses for a raport between Christianity and sages of the Synagogue. This Christian master has had enormous gains by contacts with the Rabbis. The whole church benefitted from it in interpreting the Scripture. Importance of Targum for interpretation of the NT is being accepted today. Experience, past and present, invites us to interfaith-dialogue with Judaism for a scriptural exegesis rooted in its native ‘Sitz im Leben.’